Theoretical study of spectroscopy and photodynamics of decatetraene as a representative dimethylated polyene - Chattopadhyay, Anjan; Menger, Maximilian; Sisodiya, Dilawar Singh; Köppel, Horst (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2025)
The photodynamics and UV spectroscopy of decatetraene following excitation to the bright 1Bu state are studied theoretically, based on ab initio computations of the underlying potential energy (PE) surfaces. Both photophysical and photochemical aspects are investigated. The former involves smaller amplitude displacements, and - in addition to determining multidimensional PE surfaces - also a quantal treatment of the ensuing nuclear dynamics. The inclusion of the 1Bu-2Ag vibronic interaction allows to compute the vibrational structure of the 1Ag-1Bu UV spectral band and the femtosecond 1Bu-2Ag internal conversion (population transfer). The results are compared with analogous features of octatetraene and octatriene. The photochemical aspects involving larger-amplitude displacements are investigated from a quantum-chemical point of view, focusing on the stationary points and the seams of conical intersections that are involved. A comparison of decatetraene with octatetraene reveals the contrasting features of their 2Ag and 1Bu state minima, where the latter is more stable in the dimethylated system. The small barrier connecting these two states lies between 0.06 and 0.11 eV. The nonradiative decay channels originating from these minima are characterized by comparatively higher barriers in decatetraene and influence the outcome of the radiative processes in a different manner in comparison to that of octatetraene.
Gesehen am 22.07.2025